The Preparation and Characterization on Natural Dyes Based on Neem, Henna and Turmeric for Dyeing on Cotton with Superhydrophobic Coating - Singam, Rupashinii Thana; Marsi, Noraini; Mamat, Hasri; Mohd Rus, Anika Zafiah; Main, Nor Mazlana; Huzaisham, Nur Athirah; Mohd Fodzi, Muhammad Haikal (International Journal of Integrated Engineering, 2019)
This study is presents the preparation and characterization on natural dyes based on neem, henna and turmeric for dyeing on cotton with superhydrophobic coating. Natural dyes were used to reduce the usage of the synthetic dyes in dyeing process and superhydrophobic coating to maintain the colour of the dyes on the fabric from faded and acts as a self-cleaning. The methodology involved for this study was the extraction process of natural dyes from the neem, henna and turmeric. There are eight different concentrations consists of 0.25g/ml, 0.5g/ml, 0.75g/ml, 1.0g/ml, 1.25g/ml, 1.50g/ml, 1.75g/ml and 2.0g/ml. The mechanical test involved is abrasion test for evaluation the resists wear caused by flat rubbing contact with another materials. Henna coated cotton fabrics have lower percentage weight loss compared to neem and turmeric coated cotton fabrics and uncoated cotton fabrics. The weight percentage loss for henna coated cotton fabrics at 2.0g/ml was 3.57%, for neem coated cotton fabrics at 2.0g/ml was 3.58% and turmeric at 2.0g/ml concentration was 3.59%. On the other hand, the value for the henna uncoated cotton fabric at 2.0g/ml was at 4.62%, neem at 2.0g/ml concentration was 4.64% and the value for uncoated turmeric at 2.0g/ml was 4.65% respectively.